Behind the Scenes: Mechanisms Regulating Climatic Patterns of Dissolved Organic Carbon Uptake in Headwater Streams. Issue 10 (22nd October 2018) - Catalán, N.; Casas‐Ruiz, J. P.; Arce, M. I.; Abril, M.; Bravo, A. G.; del Campo, R.; Estévez, E.; Freixa, A.; Giménez‐Grau, P.; González‐Ferreras, A. M.; Gómez‐Gener, Ll.; Lupon, A.; et al.
Abstract: Large variability in dissolved organic carbon (DOC) uptake rates has been reported for headwater streams, but the causes of this variability are still not well understood. Here we assessed acetate uptake rates across 11 European streams comprising different ecoregions by using whole‐reach pulse acetate additions. We evaluated the main climatic and biogeochemical drivers of acetate uptake during two seasonal periods. Our results show a minor influence of sampling periods but a strong effect of climate and dissolved organic matter (DOM) composition on acetate uptake. In particular, mean annual precipitation explained half of the variability of the acetate uptake velocities ( Vf Acetate ) across streams. Temperate streams presented the lowest Vf Acetate, together with humic‐like DOM and the highest stream respiration rates. In contrast, higher Vf Acetate were found in semiarid streams, with protein‐like DOM, indicating a dominance of reactive, labile compounds. This, together with lower stream respiration rates and molar ratios of DOC to nitrate, suggests a strong C limitation in semiarid streams, likely due to reduced inputs from the catchment. Overall, this study highlights the interplay of climate and DOM composition and its relevance to understand the biogeochemical mechanisms controlling DOC uptake in streams. Plain Language Summary: Headwater streams receive and degrade organic carbon and nutrients from the surrounding catchments. That degradation can be assessed by measuring the uptake of simple compounds of carbon or nitrogen such as acetate or nitrate. Here we determine the variability in acetate and nitrate uptake rates across headwater streams and elucidate the mechanisms behind that variability. The balance between nutrients, the composition of the organic materials present in the streams, and the climatic background is at interplay. Key Points: Across ecoregions, mean annual precipitation predicts 50% of the variability in dissolved organic carbon uptake The interplay between dissolved organic matter composition and nutrients availability underlies the climatic pattern and drives uptake Dissolved organic carbon uptake (as acetate) is negatively related to ecosystem respiration across regions